Evaluation of the Use of Influencer Marketing in Increasing Brand Awareness - Lesmana, Aditya (CV. Ulil Albab Corp, 2024)
This research evaluates the effectiveness of using influencer marketing in increasing brand awareness. In the digital era, influencer marketing has become an important strategy for many brands to reach a wider audience and increase engagement. Through analysis of effectiveness, engagement, reach, authenticity, and ROI, this research found that influencers who have high credibility and a strong follower base can significantly increase brand awareness. However, the success of the campaign also depends heavily on selecting the right influencer and the alignment of the influencer with the brand values. These findings emphasize the importance of a planned and measurable strategy in implementing influencer marketing to achieve optimal results.